2004
DOI: 10.1002/chem.200400316
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of PIII Ligands in the Conjugate Addition of Diorganozinc Derivatives to Enones

Abstract: A mechanistic study on the conjugate addition of diethylzinc to cyclohexenone catalyzed by various chiral PIII ligands, provides new insights into its mechanism. Complete in situ conversion of the catalytic amount of Cu(OTf)2 into CuI species by excess ZnEt2 is demonstrated by EPR spectroscopy. Experimental evidence is presented in favor of a critical ternary 1:1:1 complex between enone, Et2Zn and catalyst, supporting a rate-limiting reductive elimination or carbocupration from a preformed mixed Cu/Zn cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 55 publications
2
52
0
2
Order By: Relevance
“…[9] In two other cases (C 2 and C 3 ) an additional equivalent of L B or ZnMe 2 was included to test recent mechanistic suggestions by Schrader. [8] In all but one case (C 1 ), very significant increases of the ground-state energy are encountered-these are highly unlikely compatible with the observed efficient catalysis at low temperatures. The closest energetic species to B 1 is p-complex C 1 , which is essentially identical to the proposal of Gschwind for the catalyst rest state in 1,4-additions to cyclohexenone.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…[9] In two other cases (C 2 and C 3 ) an additional equivalent of L B or ZnMe 2 was included to test recent mechanistic suggestions by Schrader. [8] In all but one case (C 1 ), very significant increases of the ground-state energy are encountered-these are highly unlikely compatible with the observed efficient catalysis at low temperatures. The closest energetic species to B 1 is p-complex C 1 , which is essentially identical to the proposal of Gschwind for the catalyst rest state in 1,4-additions to cyclohexenone.…”
Section: Resultsmentioning
confidence: 94%
“…The closest energetic species to B 1 is p-complex C 1 , which is essentially identical to the proposal of Gschwind for the catalyst rest state in 1,4-additions to cyclohexenone. [9] On the basis of kinetic experiments on ZnEt 2 additions to cyclohexenone performed in 2004, [8] Schrader et al had suggested a structure equivalent to C 2 . However, this looks unlikely to be attained in our case due to its relative instability compared to the enone and/or ligand dissociation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[130] Nach ersten Studien [114,[131][132][133] wurde die Art des Phosphoramidit/Kupfer-Katalysators für konjugierte Additionen durch umfangreiche NMR-und MS-Experimente untersucht (Schema 9). [134][135][136] [133] die den aktiven Katalysator A regeneriert und das Zinkenolat E liefert. Die Zwischenverbindung E kann anschließend mit verschiedenen Elektrophilen zu 27 umgesetzt (siehe Abschnitt 3.1.2) oder zum einfachen Additionsprodukt 26 protoniert werden.…”
Section: Neue Entwicklungenunclassified
“…[16b] As demonstrated in Table 3 and Figure 4, GC yields for 7c and [RuCl 2 3 )] 2 exhibited higher activity to give the corresponding b-oxo esters from prop-2-yn-1-ol and various a-hydroxy carboxylic acids in 69-60% yields (80 8C, 10-24 h).…”
Section: Complex [Rucl 2 a C H T U N G T R E N N U N G (Pcymene)a C Hmentioning
confidence: 97%